Carbon Dioxide Conversion: Tailoring CO2 Reduction with Doped Silicon Nanocrystals (Adv. Sustainable Syst. 11/2017). (17th November 2017) - Wong, Annabelle P. Y.; Sun, Wei; Qian, Chenxi; Jelle, Abdinoor A.; Jia, Jia; Zheng, Ziqi; Dong, Yuchan; Ozin, Geoffrey A.
Abstract : The conversion of CO2 into solar fuels usually requires unsustainable materials. In article number1700118, Geoffrey A. Ozin and co‐workers demonstrate gas‐phase CO2 reduction using hydride‐terminated boron‐ and phosphorus‐doped silicon nanocrystals, which consist of earth‐abundant and non‐toxic elements. The CO2 reduction activity of silicon nanocrystals is successfully doubled with the addition of dopants. Cover illustrator: Chenxi Qian.